Model for measuring the risk of corporate failure: SMEs in Colombia, a case study (2019)
The paper shows a mathematical description of the operational and logistic regression technique based on lectures by authors who have profoundly worked its empirical application. The concept of credit risk is defined in a statistical context. A description of economic activities considered in the study. Then, construction was synthesized in 19 SPSS logistic regression model: definition of group training and selection of variables related to business solvency. Finally,results are presented in tables, with the coding of variables, statistical goodness of fit and predictive power to determine the probability that an SME company insolvent fall and create a risk to creditors. It was found that companies reported accumulated losses are eight times more likely to fall insolvent companies with positive retained earnings.